PENGARUH KOMPENSASI BONUS DAN DIVIDEND PAYOUT RATIO TERHADAP PRAKTIK PERATAAN LABA: (Studi pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2019) - Maulinda Zulfa Rahmania; Ade Irma Suryani Lating; Selvia Eka Aristantia (Media Mahardhika, 2022)
This study aims to determine the effect of bonus compensation and dividend payout ratio on income smoothing practices. This research is a quantitative research with an associative approach. The data testing techniques used are partial hypothesis testing (t test), simultaneous hypothesis testing (F test) and multiple linier regression analysis using SPSS software version 25. The number of samples tested in this study were 66 samples consisting of 33 companies with research period of 2 years. The data used in this research are secondary data sourced from IDX official website and official website of related companies. The results showed that partially, bonus compensation had no effect on income smoothing practices, but dividend payout ratio had a significant negative effect. Meanwhile, simultaneously, bonus compensation and dividend payout ratio have a significant effect on income smoothing practices. Based on these results, it is hoped that investor and potential investor will be more thorough in analyzing and identifying the company, and not seeing the company only by the value of dividends or the amount of profit that generated by banking companies which will later be used as investment destinations.